White-Tailed Eagle in the Republic of Tatarstan – Continuation of Research - Rinur H. Bekmansurov; Nadezhda V. Bekmansurova; Evgeny S. Kostin; Yuri A. Gorshkov; Igor V. Karyakin (Пернатые хищники и их охрана)
The White-Tailed Eagle (Haliaeetus albicilla) has been a key species for projects on study and conservation of large raptors in Tatarstan, which has been continuously carried out since 2011. The main monitoring studies were carried out in the upper part of Kuibyshev and Nizhnekamsk reservoirs, where large population groups have been formed since the end of the 20th century. Protected areas were the main monitoring plots. Currently, the section “Raptors of the World” of the web GIS “Faunistics” contains data on 210 White-Tailed Eagle breeding territories in Tatarstan.